Selection of Bacillus spp. for Cellulase and Xylanase Production as Direct-Fed Microbials to Reduce Digesta Viscosity and Clostridium perfringens Proliferation Using an in vitro Digestive Model in Different Poultry Diets - Latorre, Juan D.; Hernandez-Velasco, Xochitl; Kuttappan, Vivek A.; Wolfenden, Ross E.; Vicente, Jose L.; Wolfenden, Amanda D.; Bielke, Lisa R.; Prado-Rebolledo, Omar F.; Morales, Eduardo; Hargis, Billy M.; Tellez, Guillermo (Frontiers in Veterinary Science, 2015)
Previously, our laboratory has screened and identified Bacillus spp. isolates as direct-fed microbials (DFM). The purpose of the present study was to evaluate the cellulase and xylanase production of these isolates and select the most appropriate Bacillus spp. candidates for DFM. Furthermore, an in vitro digestive model, simulating different compartments of the gastrointestinal tract, was used to determine the effect of these selected candidates on digesta viscosity and Clostridium perfringens proliferation in different poultry diets. Production of cellulase and xylanase were based on their relative enzyme activity. Analysis of 16S rRNA sequence classified two strains as B. amyloliquefaciens and one of the strains as B. subtilis. The DFM was included at a concentration of 108 spores/g of feed in 5 different sterile soybean-based diets containing corn, wheat, rye, barley, or oat. After digestion time, supernatants from different diets were collected to measure viscosity, and C. perfringens proliferation. Additionally, from each in vitro simulated compartment, samples were taken to enumerate viable Bacillus-spores using a plate count method after heat-treatment. Significant (P<0.05) DFM-associated reductions in supernatant viscosity and C. perfringens proliferation were observed for all non-corn diets. These results suggest that antinutritional factors such as non-starch polysaccharides from different cereals can enhance viscosity and C. perfringens growth. Remarkably, dietary inclusion of the DFM that produce cellulase and xylanase reduced both viscosity and C. perfringens proliferation compared with control diets. Regardless of diet composition, 90% of the DFM spores germinated during the first 30 min in the crop compartment of the digestion model, followed by a noteworthy increased in the intestine compartment by ~2 log10, suggesting a full-life cycle development. Further studies to evaluate in vivo necrotic enteritis effects are in progress.